Moving Cultures: Engaging Refugee and Migrant Culture Rights in International Heritage Law - Lixinski, Lucas (UI Scholars Hub, 2018)
In thinking about the rise of the Anthropocene, an important facet of this looming new era remains under-explored: namely, how cultural identity, and its tangible and intangible markers, are to be renegotiated and protected. Notwithstanding that the origins of international heritage law lie in protecting heritage in times of crisis (wartime and natural or man-made disasters), regimes under UNESCO for safeguarding cultural heritage in international law are ill-prepared for the challenges of the Anthropocene. A particular question that needs to be considered is the protection in international law of cultural heritage and identity when communities are displaced from their homes. Because international cultural heritage law is connected to state territoriality, states have the ultimate authorizing power over the meanings and uses of cultural heritage. In the past, this power has at times been used to the detriment of minority groups contesting the majoritarian state. But how might this power play out in a context where communities are forced to move? What, if anything, can international heritage law do to ensure that these populations, who have already lost their homes and livelihoods, can maintain their cultural identity through the protection of their heritage? I argue that international law’s separation between the cultural and biological facets of human existence presents a major obstacle to safeguarding the cultures of migrant and refugee groups, ultimately frustrating the very objectives that this separation was meant to achieve, namely, the protection of these populations. Only by reintegrating biology and culture can international law create the means for reimagining civilization in the Anthropocene.